Diagnóstico y auditoría energética en la Empresa Lácteos la Polaca Gustalac S.A. - Anzules Soliz, Edinson Daniel (2022)
This research document collects and presents data which allows an analysis of energy quality in the company La Polaca Gustalac S.A, in order to know the current energy state and propose possible solutions which will improve the efficiency and use of energy. In the company, the data will be analyzed under the criteria and quality limits of ARCONEL 005/18, which indicates the correct or deficient use of energy, in the data collection obtained by the network analyzer both on the 220v side and 420v of the transformer it was known that one of the big problems of the company are the harmonics themselves that cause affectation in the equipment and machinery, for this reason a harmonic filter was designed to correct the effects caused by this phenomenon and thus be within the standards and limits allowed according to the current regulation.